(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Helicobacter pylori (H. pylori) is amongst the most infectious and almost half of the country’s population is affected by a chronic bacterial infection. H. pylori evoke an inflammatory reaction of the host epithelium, leading to induction of immune cells which exhibit as gastritis. There is little knowledge of how • pylori remain in the host’s antimicrobial agents, such as calprotectin (CP), which is found through an immune response. Objective: The purpose of this study was to evaluate the role of fecal calprotectin (FC) in subjects with gastric ulcer and correlation of it with H. pylori. Methods: 25 patients with gastric ulcer and 25 healthy controls were included in a prospective study. Samples of blood are taken IgG antibody H pylori and stool specimen for measured of calprotectin level. Results: All gastric ulcer patients infected with H pylori. From a total of 25 patients participating in this study 8 were man and 17 women with the mean age 40.6±15.8. There was a statistically meaningful difference between the groups analyzed (p=0.0001) dependent on the calprotectin level. Also found significant association between sex and calprotectin level according to the positivity of H pylori.Conclusion: There’s a significant statistical between fecal calprotectin level and H. pylori infection in gastric ulcer patients.